Research on Scenarios and Modeling of Co-Frequency Interference Between NGSO Communication Constellation Systems - Wei LI; Kang YAN; Jingru GENG; Wen WANG (天地一体化信息网络)
Aiming at the serious problem of frequency overlapping among non-geostationary satellite orbit (NGSO) communication constellation systems.The potential interference scenarios under multiple NGSO communication constellation systems sharing the same spectrum band was comprehensively analyzed, with the aid of analyzing frequency plan of typical constellation systems.Then the possibility of interference risk in each scenario was qualitatively evaluated.According to the characteristics of interference scenarios, the key parameters and models for the co-frequency interference analysis between the NGSO communication constellation systems were discussed, and the computing models of co-frequency interference based on three diff erent protect criterion were presented.Finally, challenges and key research directions of co-frequency interference analysis between NGSO communication constellation systems were pointed out.The research can provide a reference for the study of compatibility and coexistence between broadband Internet constellation systems.